1980
DOI: 10.1149/1.2129962
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Absorption and Microstructure of Li‐Saturated Si‐Doped GaAs

Abstract: Infrared absorption, free carrier density, and transmission electron microscopy measurements have been correlated for n-type Si-doped GaAs samples with 1 • 10 is cm-~ < [Si] < 5 X 1019 cm -3. The infrared absorption of the localized vibrational modes was measured after the samples were compensated by e-irradiation or by 6Li saturation diffusion. Comparisons of the results of the two compensation methods indicate that: (i) the Li-native defect acceptor complex is responsible in large part for the compensation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…(After Woodhouse and Newman (1993)J and . The disposition of the lines is similar to those found for SiGa-LiGa (Chen and Spitzer 1980), Si,,-Zn, (Allred et al 1969) and Si,,-Cu,, (Spitzer et a1 1969) donor-acceptor second-neighbour pairs, leading to the conclusion that SiGs-YGZ also has C, point symmetry and that the component Y, . is an acceptor.…”
Section: Localized Vibrational Modes Of Silicon Impurities In Gaassupporting
confidence: 73%
“…(After Woodhouse and Newman (1993)J and . The disposition of the lines is similar to those found for SiGa-LiGa (Chen and Spitzer 1980), Si,,-Zn, (Allred et al 1969) and Si,,-Cu,, (Spitzer et a1 1969) donor-acceptor second-neighbour pairs, leading to the conclusion that SiGs-YGZ also has C, point symmetry and that the component Y, . is an acceptor.…”
Section: Localized Vibrational Modes Of Silicon Impurities In Gaassupporting
confidence: 73%
“…Chen and Spitzer 19 reported Si site switching in originally n-type Si-doped GaAs which had been Li indiffused and subsequently annealed. They concluded that the presence of Li could cause the transfer of Si from a Ga lattice site to an As lattice site.…”
Section: Discussionmentioning
confidence: 99%
“…do not occur in concentrations sufficient to detect. In the above studies, optical measurements of the infrared absorption produced by the localised vibrational modes of the defects were used with other measurements, such as the Hall effect and transmission electron microscopy (Chen and Spitzer 1980), to help establish the probable defect structure. 0022-37191821275593 + 12 $02.00 @ 1982 The Institute of Physics 5593 There has been very little experimental work (Mitsuishi et a/ 1966.…”
Section: Introductionmentioning
confidence: 99%